The Political Participation of Women: A Guarantee of Respect for True Democracy - Bolaños Moreno, Mónica Estefanía (2025)
This article highlights the central role of women in society and in the public sphere. It primarily analyzes the political participation of women as a fundamental axis to achieve a much more effective and inclusive democracy. First, the historical gaps that have limited women's access to decision-making spaces are addressed, highlighting how these inequalities undermine democratic principles. Then, the regulatory advances are explored, specifically, in the Organic Electoral and Political Organizations Law of the Republic of Ecuador, Code of Democracy, which have allowed a much more solid female representation in politics, although challenges persist in its implementation.